Determination of the Significance of the Most Effective Nutrients on Lipase Production from Cryptococcus albidus D24 - PİNAR, ORKUN; KAZAN, DİLEK; Uras, Abdussamed (My University, 2022)
In this study, the optimization of the medium components used for the production of lipase enzyme from Cryptococcus albidus D24 was performed using the Plackett-Burman statistical design method (PBD), and the most important nutrients affecting the production of lipase enzyme from D24 strain were determined as the first step. According to PBD, the highest lipase activity (19.34 U/ml/min) was obtained with medium including Tween 80 (X2) 2.5% (v/v), and (g/L) Peptone (X4) 8.0, Yeast Extract (X6) 7.5, Beef Extract (X7) 7.5, Malt Extract (X8) 7.5, NH4Cl (X9) 6.0, NaNO3 (X10) 1.5, (NH4)NO3 (X12) 6.0, (NH4)HCO3(X13) 6.0, MgSO4.7H2O (X15) 1.0, and KH2PO4 (X16) 2.0 at the end of 144 h cultivation. Regarding the concentration effect (CE) values obtained from PBD, NH4Cl (CE=7.1587), olive oil (CE=3.5544), (NH4)HCO3 (CE=3.0747), and tryptone (CE=2.1427) were evaluated as the more effective nutrients among the sixteen compounds studied. After that, the optimum concentrations of these effective compounds were experimented with Response Surface Methodology (RSM). Experimental results showed that the medium containing olive oil (X3) 1.5% (v/v), and (g/L) tryptone (X5) 3.0, NH4Cl (X9) 7.5, and (NH4)HCO3 (X13) yielded maximum lipase activity (12.03 U/ml/min) compared to other studied compounds. Although the maximum lipase activity obtained with RSM methodology was lower than that obtained by PBD, the cost of the nutrients used to produce one-unit enzyme is 0.104 Euro in the PBD, while only 0.0277 Euro is spent in RSM. In other words, the production of lipase using compounds coded X3, X5, X9, and X13 provides a cost-effective process.

Bu çalışmada, Cryptococcus albidus D24'ten lipaz enzimi üretimi için kullanılan besiyeri bileşenlerinin Plackett-Burman İstatistiksel Tasarım Yöntemi (PBD) kullanılarak optimizasyonu gerçekleştirilmiş ve ilk adım olarak D24 suşundan lipaz enzimi üretimine etki eden en önemli besin maddeleri belirlenmiştir. PBD'ye göre en yüksek lipaz aktivitesi (19,34 U/ml/dk), Tween 80 (X2) %2,5 (h/h) ve (g/L) Pepton (X4) 8.0, Maya özütü (X6) 7.5, Et ekstraktı (X7) 7.5, Malt Ekstrakt (X8) 7.5, NH4Cl (X9) 6.0, NaNO3 (X10) 1.5, (NH4)NO3 (X12) 6.0, (NH4)HCO3 (X13) 6.0, MgSO4.7H2O (X15) 1.0 ve KH2PO4 (X16) 2.0 bileşenlerini içeren ortam ile 144 saat sonunda elde edilmiştir. PBD'den elde edilen konsantrasyon etkisi (CE) değerlerine göre incelenen on altı bileşik arasında, NH4Cl (CE=7.1587), zeytinyağı (CE=3.5544), (NH4)HCO3 (CE=3.0747) ve tripton (CE=2.1427) daha etkili olarak bulunmuştur. Daha sonra belirlenen bu etkili bileşiklerin optimum konsantrasyonları, Yanıt Yüzey Yöntemi (RSM) ile belirlenmiştir. Deneysel sonuçlara göre, zeytinyağı (X3), tripton (X5), NH4Cl (X9) ve (NH4)HCO3 (X13) bileşenleri, sırasıyla %1,5 (h/h), 3.0 g/L, 7.5 g/L ve 12.0 g/L konsantrasyonlarında maksimum lipaz aktivitesi (12.03 U/ml/dak) elde edildiği ve bir (1) ünite enzim aktivitesi elde etmek için, hammadde maliyetinde bir azalma sağlanabileceği gösterilmiştir.
Cryptococcus albidus D24'ten Lipaz Üretimi Üzerindeki En Etkili Besin Maddelerinin Öneminin Belirlenmesi
Keywords: Kimya Mühendisliği ve Teknolojisi; Biyoteknoloji; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Biotechnology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences